ANALISIS TOTAL MIKROBA, MUTU FISIK, DAN SENSORIS SIRUP KAWISTA DENGAN PENAMBAHAN KAYU SECANG - Ambar Kusumawati; Agus Suyanto (Jurnal Pangan dan Gizi, 2023)
The syrup is a beverage product made from a mixture of water and sugar with or without the addition of food additives that are allowed under applicable regulations. However, some syrup products use food additives such as preservatives that exceed the standard limits that have been allowed to reduce the quality of the syrup. Secang wood is known to be able to minimize microbial growth in syrup products. The purpose of this study is to determine the effect of the addition of secang wood on the total microbes, physical quality, and sensory quality of kawista (Feronia limonia) syrup. The experimental type of research method uses a factorial Complete Randomized Design (RAL), which consists of 1 factor 5 treatments, namely the concentration of secang wood 0, 5, 10, 15, and 20%. Each treatment was repeated 5 times so that 25 experimental units were obtained. The steps taken are starting with the process of making secang wood boiled water, then making kawista syrup with the addition of a concentration of secang wood. The results showed that there was an influence of the addition of secang wood on the total microbes, physical quality, and sensory (color, aroma, and viscosity) of kawista syrup. In addition, there is no effect of adding secang wood on the taste of kawista syrup. The best treatment was obtained from a concentration of 20% secang wood which produced total microbes (2,0 x 106 CFU/ml), pH (7.2), viscosity (12.14 mPa.S.), and hedonic quality (3,96).